Consumo de fórmulas nutricionales para adultos, comercializados en un establecimiento farmacéutico de la ciudad de Piura, durante el año 2016 - Gutiérrez Toribio, Cristian Paolo (2017)
The following report presents data on the consumption of nutritional formulas for adults, marketed in a pharmaceutical establishment belonging to the INKAFARMA apothecary chain, located in the department of Piura, where the pre-professional practices were carried out, in 2016. The data were provided by the kardex system, which allows obtaining information on the consumption of different brands of nutritional formulas with a higher degree of commercialization. Some of these brands are Ensure, Ensure Advance and Glucerna de Lab. Abbott; Vital Vitamin from Lab. Lypack and Geriaplus from Lab. Pro Nutrition Peru, these last two brands are exclusive to the Inkafarma chain. Geriaplus is the nutritional formula for adults, with the highest monthly and annual consumption for the year 2016, at the mentioned pharmaceutical establishment